Learning History on High School Equivalency Program - Ranulin Windarsari; Sunardi Sunardi; Djono `Djono (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2017)
This study is aimed to describe the implementation of learning history in high school equivalency programs. This study uses the descriptive qualitative method. Data were collected by interviews, documentation, and observation. Data analysis technique use qualitative analysis inductive models with purposive sampling technique. The results of this study are: first, planning learning history in high school equivalency program started from In-House Training for educators in high school equivalency program which practiced in the preparation of the learning device are appropriate to the curriculum; second, the implementation of learning history in high school equivalency program involves three patterns of learning consisting of 20% face-to-face interaction, 30% tutorials, and 50% independent activity; third, constraints in the implementation is the readiness of learners in receiving learning materials, learning infrastructure, and the competence of educators in conveying the teaching of history; fourth, evaluation of learning history in high school equivalency program is equal to the formal school.